An Intrinsically Stretchable High‐Performance Polymer Semiconductor with Low Crystallinity. (12th September 2019) - Zheng, Yu; Wang, Ging‐Ji Nathan; Kang, Jiheong; Nikolka, Mark; Wu, Hung‐Chin; Tran, Helen; Zhang, Song; Yan, Hongping; Chen, Hu; Yuen, Pak Yan; Mun, Jaewan; Dauskardt, Reinhold H.; et al.
Abstract: For wearable and implantable electronics applications, developing intrinsically stretchable polymer semiconductor is advantageous, especially in the manufacturing of large‐area and high‐density devices. A major challenge is to simultaneously achieve good electrical and mechanical properties for these semiconductor devices. While crystalline domains are generally needed to achieve high mobility, amorphous domains are necessary to impart stretchability. Recent progresses in the design of high‐performance donor–acceptor polymers that exhibit low degrees of energetic disorder, while having a high fraction of amorphous domains, appear promising for polymer semiconductors. Here, a low crystalline, i.e., near‐amorphous, indacenodithiophene‐ co ‐benzothiadiazole (IDTBT) polymer and a semicrystalline thieno[3, 2‐ b ]thiophene‐diketopyrrolopyrrole (DPPTT) are compared, for mechanical properties and electrical performance under strain. It is observed that IDTBT is able to achieve both a high modulus and high fracture strain, and to preserve electrical functionality under high strain. Next, fully stretchable transistors are fabricated using the IDTBT polymer and observed mobility ≈0.6 cm 2 V −1 s −1 at 100% strain along stretching direction. In addition, the morphological evolution of the stretched IDTBT films is investigated by polarized UV–vis and grazing‐incidence X‐ray diffraction to elucidate the molecular origins of high ductility. In summary, the near‐amorphous IDTBT polymer signifies a promising direction regarding molecular design principles toward intrinsically stretchable high‐performance polymer semiconductor. Abstract : Herein, a low crystalline indacenodithiophene‐ co ‐benzothiadiazole (IDTBT) donor–acceptor copolymer is reported to be able to preserve electrical functionality under high strain. The mechanical properties and morphological evolution for IDTBT thin films during stretching is systematically investigated. This kind of near‐amorphous polymer signifies a promising direction regarding molecular design principles toward intrinsically stretchable high‐performance polymer semiconductors.